Methodology for biorefinery portfolio assessment using supply‐chain fundamentals of bioproducts. (23rd April 2014) - Dansereau, Louis Patrick; El‐Halwagi, Mahmoud; Chambost, Virginie; Stuart, Paul
Abstract Given the emergence of innovative processes in recent years for the manufacture of bioproducts from second‐generation biomass, a range of unique biorefinery strategies are likely to be implemented by forest product companies in the coming years. No matter what biorefinery strategy is employed, to compete in the longer term, it will be critical to have a supply‐chain adapted to the targeted products. In order to meet customer needs and at the same time be cost‐competitive, there are trade‐offs to be made between responsiveness and efficiency in several areas of the supply chain, such as production and customer service. This paper reviews supply‐chain characteristics and competitive factors for various bioproducts. An approach that can be used by decision‐makers during early‐stage design is presented, suitable for screening‐out less promising options based on their supply‐chain characteristics. Fundamental aspects such as the differentiation of products, their possible green advantage, biomass procurement, and process characteristics are discussed within five categories: bioenergy, biofuels, commodity biochemicals, fine and specialty biochemicals, and biomaterials. Several examples of biorefinery strategies are discussed to illustrate these concepts.